VITAMIN D DEFICIENCY IN PREGNANCY: EFFECT ON MATERNAL AND FETAL OUTCOME - USHA KUMARI; RAJ KISHOR SHARMA; ARCHANA SINHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Vitamin D deficiency (VDD) during pregnancy is known to affect the neonatal morbidity and mortality. This study was conducted in pregnant women with the aim of assessing the prevalence of VDD in pregnant women and its effect on expecting mother and newborn. Methods: This was a cross-sectional study done over a period of 2 years. 25(OH)D3 level was tested by Chemiluminescent Immunoassay in clinical biochemistry laboratory. Subjects were classified into Vitamin D-deficient, insufficient, and sufficient group. Results: Mean level of Vitamin D in the study population was 21.82±12.95. The level of Vitamin D was found to be sufficient only in 28% (28/100) of subjects. A significant correlation was observed between newborn birth weight and serum Vitamin D level of the mother. Appearance, pulse, grimace, activity, and respiration (APGAR) score was moderately and severely depressed in 17% and 3% of babies, respectively. Pre-eclampsia was observed in 8% (8/100) of the subjects. A significant correlation was observed between the occurrence of pre-eclampsia and maternal Vitamin D. APGAR score was found to be significantly associated with serum Vitamin D. Conclusion: There is a high prevalence of VDD in pregnant women. VDD in pregnancy is associated with several complications to the expectant mother as well as the fetus. Complications such as pre-eclampsia, low birth weight (LBW) babies, and low APGAR score were observed in the present study. There is a need of extensive clinical research on the impact of VDD in pregnancy on mother and fetal health.